Hardware-in-the-loop Simulation Platform of Photovoltaic Grid-Connected System - Lin FENG; Qing ZHONG; Nanhua YU; Kun WANG; Guojie LI; Kan CHEN (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The modeling and simulation of photovoltaic power generation system has become an important issue in the field of power generation. Research on the characteristics of photovoltaic (PV) grid-connected system by hardware-in-the-loop simulation could provide convenient experiment condition and accurate result. This article designs a photovoltaic grid-connected simulation platform for digital/physical hybrid real-time simulation, in which RTDS uses a digital-to-analog interface to communicate with external DSP devices. Maximum power point tracking (MPPT) and grid-connected control of a 520kWp PV system are performed on the platform. And the feasibility and effectiveness of hybrid PV system are validated by the analysis of hardware-in-the-loop result in RTDS. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4794